Modern recording techniques - Huber, David Miles (Routledge, 2018)
Modern Recording Techniques is the bestselling, authoritative guide to sound and music recording. Whether you’re just starting out or are looking for a step-up in the industry, Modern Recording Techniques provides an in-depth read on the art and technologies of music production. It’s a must-have reference for all audio bookshelves. Using its familiar and accessible writing style, this ninth edition has been fully updated, presenting the latest production technologies and includes an in-depth coverage of the DAW, networked audio, MIDI, signal processing and much more.